Effect of Tooth Surface Friction on Bending Torsional Axial Pendular Coupling Nonlinear Amplitude Frequency Characteristic of Marine Herringbone Gear - Haoqin Zhang; Hao Dong; Libang Wang; Xiaolong Zhao (Jixie chuandong)
In order to analyze the nonlinear amplitude frequency characteristics of marine herringbone gear transmission system more accurately， the factors such as tooth surface friction， time-varying meshing stiffness， backlash， comprehensive transmission error， external load excitation， intermediate shaft section and elastic support are comprehensively considered， a bending torsional axial pendular nonlinear dynamics model of 24-DOF marine herringbone gear transmission system is established based on the lumped mass parameter method， and the nonlinear dynamic differential equations of the system are derived. In the model， the friction coefficient， friction force and friction moment are calculated by using the elastohydrodynamic lubrication theory. The Runge-Kutta numerical method is used to solve the differential equation. The phase diagram and time history diagram of the non-dimensional frequency system under the influence of tooth surface friction are obtained. The influence of tooth surface friction on the nonlinear frequency response characteristics of the system is analyzed. The results show that the tooth surface friction suppresses the vibration of the herringbone gear pair along the meshing line， but does not change the meshing state of the gear; in different meshing frequency range， low frequency range of 0~0.89 and high frequency range of 1.42~2， the damping effect of tooth surface friction on vibration amplitude cannot be ignored. In the non-stationary resonance range of dimensionless meshing frequency of 0.95~1.23， the damping effect of tooth surface friction is not obvious. It provides a theoretical basis for the study of vibration and noise reduction performance of herringbone gears.